Development of models and research into tooling for machining centers - Krol, Oleg; Sokolov, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2018)
We have constructed three-dimensional solid models for tool storage of the disk type (for 14 instruments) and the chain type for 32 tools, mounted onto the side surface of a machine column. We propose a 3D model of the tool positioner with a hydraulic cylinder that performs an automated tool change. The generated set of models for tooling, in combination with models of tool storage and tool positioners, represents the entire complexity and special features of design and technological preparation of machining processes at machining centers of standard size III and IV. We have developed models and algorithms for parametric modeling of basic elements of profile cutting tools. Using the built-in parametrizer in the APM Graph module makes it possible to implement a simpler approach to constructing models for unified profiles of tools in order to speed up the process of creating specialized application libraries. We have built analytical models for determining the rigidity of shape-forming machine nodes. Such an approach is most effective for typical circuits of double-support spindles that are equipped with various tooling. In contrast to the generally accepted procedure, the proposed analytical models (static backlogs) provide for obtaining express estimations for the optimum correlation between design parameters of spindle nodes. Such an approach to research is defined by a tendency toward expanding technological possibilities of machining centers equipped with a constantly changing range of tooling. The emergence of new kinds of industrial tooling must be provided with methods and algorithms that interrelate the stages of constructing models of designs and assessment of their performance for the criterion of rigidity. Under conditions of machine-tool industry, the toolset proposed in this work is aimed at improving the quality of creating the three-dimensional models of structures, their photorealistic imaging, rapid adaptation to changing conditions and operative estimation of rigidity of the shape-forming nodes. Implementation of the proposed toolset is directed towards improving the competitiveness of the designed projects.